Communities of women in Assam : being, doing and thinking together - Nandana Dutta (Routledge, Taylor & Francis Group, 2016)
This book uses communities of women as a framework for reading women's experience, rights and aspirations in Assam and Northeast India. It explores the varying roles played by such communities in the formation of society, the emergence of a women's public sphere and the representation of these communities in culture. The essays in the volume study a host of women's communities including the Mahila Samiti, Jain women's organisations, Lekhika Sanstha, lesbian communities, religious gatherings, scientific and environmental groups, women's collaborations through cookbooks, as well as nebulous communities of victims of persecution. They examine how women's communities are both empowering and transformational but may paradoxically also be regressive and static. Table of Contents: Part 1: Society: 1. 'Great Sensation in Guwahati': Mini's marriage, Assam Mahila Samiti and the Sarda Act in late colonial Assam / Hemjyoti Medhi; 2. Witch-hunting and resistance to the formation of women's community / Anjali Daimari; 3. Participation in and access to the public 'sacred' space: sisterhood and the Naamghar in Assam / Juanita Kakoty; 4. Questions of space, autonomy and identity: a study of the communities of Jain women in Dibrugarh / Payal Jain; 5. Lesbian women and the politics of community formation: changing discourses on citizenship / Poonam Kakoti Borah. Part II: Culture : 6. Media representing women - women in the media : exploring possibilities of community / Asha Kuthari Chaudhuri; 7. Woman Writing Woman: a study of Pushpalata Das' 'Agnisnata Chandraprava'; 8. The Assam Lekhika Sanstha: A community of Women Writers / Dolikajyoti Sharma; 9. Nature, Science and women's community /Sutopa Raichaudhury; 10. Women, community and the material culture of food / Uttara Debi.